2009
DOI: 10.1089/ten.tea.2009.0065
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclast Differentiation Induced by Synthetic Octacalcium Phosphate Through Receptor Activator of NF-κB Ligand Expression in Osteoblasts

Abstract: Synthetic octacalcium phosphate (OCP) has a potential to enhance new bone formation and exhibits biodegradable characteristics when implanted in experimentally created bone defects. The precise mechanisms of OCP biodegradation remain unclear, though histological observations have revealed that bone-resorbing osteoclasts appear and resorb implanted OCP. To investigate how osteoclasts develop around implanted OCP, we examined osteoclast differentiation using OCP crystals in vitro. Coculturing of mouse bone marro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 47 publications
3
63
0
1
Order By: Relevance
“…Our previous studies verified that OCP has positive effects on osteoblast differentiation in mouse calvaria primary cells and ST-2 cells 13) , osteoclast formation in mouse bone marrow derived cells via osteoblastic cells 41) , and odontoblast differentiation from rat primary dental pulp cells 42) , if cells were directly incubated on OCP crystals coated on culture plates. However, these effects were reproducible when the cells were cultured on a non-OCP-coated surface in an OCP-half coated plate, suggesting that ionic soluble products from OCP modulate the cellular response 41,42) . In contrast, a study using a similar OCP coating technique and chondrogenic ATDC5 cells showed that cellular activity (inhibition of chondrogenic differentiation) occurred only if cells were in direct contact with the OCP-coated surface 43) .…”
Section: Discussionsupporting
confidence: 71%
“…Our previous studies verified that OCP has positive effects on osteoblast differentiation in mouse calvaria primary cells and ST-2 cells 13) , osteoclast formation in mouse bone marrow derived cells via osteoblastic cells 41) , and odontoblast differentiation from rat primary dental pulp cells 42) , if cells were directly incubated on OCP crystals coated on culture plates. However, these effects were reproducible when the cells were cultured on a non-OCP-coated surface in an OCP-half coated plate, suggesting that ionic soluble products from OCP modulate the cellular response 41,42) . In contrast, a study using a similar OCP coating technique and chondrogenic ATDC5 cells showed that cellular activity (inhibition of chondrogenic differentiation) occurred only if cells were in direct contact with the OCP-coated surface 43) .…”
Section: Discussionsupporting
confidence: 71%
“…Histochemical analysis revealed that TRAP staining was qualitatively higher in OCP/Col with smaller OCP granules than in that with larger granules. It has been proved that osteoclast formation can be induced on OCP coating from in vitro co-culturing in osteoblasts and bone marrow cells even in the absence of vitamin D 3 , a factor to increase osteoclast-inducing factor RANKL in osteoblasts, 16 and that TRAP-positive osteoclast-like cells resorb OCP granules. 47,48 The present results reconfirmed that osteoclast-like cells can resorb OCP granules and suggest that decreasing the granule size of OCP enhances the osteoclastic cellular activity to resorb.…”
Section: Effect Of Ocp Granule Size In Bone Substitute Materials 553mentioning
confidence: 99%
“…5 It was recently found that OCP is capable of inducing osteoclast formation from the coculturing of osteoblasts and bone marrow cells, through the increase of expression of osteoblasts of osteoclast-inducing factor RANKL, even in the absence of vitamin D 3 , a regulator of osteoclastogenesis. 16 Furthermore, OCP enhances osteoblast differentiation in vitro. [17][18][19] Our previous study showed that OCP, if synthesized under specific conditions, is not only more resorbable than sintered b-TCP in bone defects, because of osteoclastic cellular resorption, but is also more osteoconductive than b-TCP or stoichiometric and nonstoichiometric HA.…”
Section: Introductionmentioning
confidence: 99%
“…2,15 OCP is a biodegradable material that is mediated by osteoclastic resorption. 3,5 The OCP/Gel composite has been shown to have a biodegradable characteristic in critically sized rat calvaria. 10 The present results reconfirm that OCP/Gel is a highly biodegradable material if implanted in rabbit tibia.…”
Section: ) Possible Mechanism To Enhance Bone Regeneration By Ocp/gementioning
confidence: 99%
“…Octacalcium phosphate (OCP) crystals, having specific material characteristics, have been recognized to display a stimulatory capacity on osteoblast differentiation from stromal cells 1,2 and osteoclast formation from the precursor cells in co-culturing with osteoblasts 3 in vitro. In fact, OCP and OCP-based materials with natural polymers, such as OCP/collagen composite, enhance bone regeneration coupled with their own biodegradation in various experimentally created bone defects.…”
Section: Introductionmentioning
confidence: 99%